La práctica en la licenciatura en educación física como “cosa viva”: Una perspectiva a partir de la semiótica y del pragmatismo de charles s. peirce - Mendes, Diego de Sousa; Betti, Mauro [UNESP] (Universidade Federal do Rio Grande do Sul, 2017)
The study investigated the consequences of the establishment of Supervised Practicum based on Charles S. Peirce’s assumptions of Semiotics and Pragmatism. We conducted Action Research with a Supervised Practicum class in Physical Education at the Federal University of São João del-Rei (UFSJ), where we experienced a pedagogical approach inspired by Peirce’s concept of “science as a living thing” in order to enhance the formative experience during practicum. Data analysis showed that the practicum process based on communication, reflection, the drive towards research, promotion of doubt, and the pedagogical beliefs re-signification impacted on participants’ teaching behavior, making the internship experience more meaningful in terms of learning.
O estágio na licenciatura em educação física como “coisa viva”: Uma perspectiva a partir da semiótica e do pragmaticismo de charles s. peirce
Practicum in physical education school as “living thing”: A perspective from semiotics and charles S. Peirce’s pragmatism
Keywords: Internship; Physical education; Pragmatism; Semiotics